Management of Intussusceptions Secondary to Pathological Lead Points in Infants and Children - Ghritlaharey, Rajendra K. (Annals of the National Academy of Medical Sciences (India), 2021)
Objectives This study was undertaken to investigate and review the age, sex, clinical presentation, surgical procedures done, major postoperative complications, and the final outcome of infants and children operated for intussusceptions secondary to pathological lead points (PLPs).Materials and Methods This is a single-institution, retrospective study and included infants and children below the age of 12 years who were operated for the secondary intussusceptions. This study was conducted at author’s Department of Paediatric Surgery during the last 20 years; from January 1, 2000 to December 31, 2019.Results During the study period, 200 infants and children were operated for the intussusceptions, and 23 (11.5%) of them were operated for the intussusceptions secondary to PLPs. This review comprised 18 (78.26%) boys and 5 (21.73%) girls, and consisted of infants (n = 9, 39.13%) and children of 1 to 5 years of age (n = 7, 30.43%) and 6 to 12 years of age (n = 7, 30.43%). The age at presentation ranged from 3 months to 10 years, with the mean age of 41.47 ± 40.06 months. Clinically, all the children presented with features of acute intestinal obstruction. Ultrasonography (USG) examination of the abdomen revealed the diagnosis of intussusception in all of them but not able to document the PLPs as a cause for it. During the exploratory laparotomies, gangrenous bowel was detected in 15 (65.21%) cases. PLPs causing intussusceptions were Meckel’s diverticulum (n = 17, 73.91%), begin ileal growth (n = 4, 17.39%), benign ileal polyp (n = 1, 4.34%), and caecal lymphoma (n = 1, 4.34%). Surgical procedures were executed in the following order of frequency: (1) resection of segment of ileum including PLP, and ileoileal anastomosis (n = 13, 56.52%); (2) resection of segment of ileum including PLP, caecum and part of ascending colon, and ileoascending anastomosis (n = 5, 21.73%); (3) Meckel’s diverticulectomy (n = 3, 13.04%); and (4) resection of segment of ileum including PLP and terminal ileostomy (n = 2, 8.69%). This study documented two (8.69%) deaths in postoperative period.Conclusion Meckel’s’ diverticulum was the commonest pathology for the secondary intussusceptions in infants and children and documented most frequently during infancy. Half of the secondary intussusceptions occurred within 24 months of age. Bowel resection was required in more than 85% of the cases during the surgical procedures.
Keywords: children; infants; intestinal obstruction; intussusception; Meckel’s diverticulum; pathological lead points; secondary intussusception